A study of prevalence of autoantibodies in lean or underweight diabetic subjects in Southern Rajasthan - Kansara, Sandeep; Hasan, Akhlaq; Goyal, Shuchi (International Journal of Research in Medical Sciences, 2022)
Background: The prevalence of diabetes mellitus (DM) is increasing day by day. Changing life style and unhealthy eating habits are major contributor to this pandemic, however certain individuals develop diabetes despite enough physical activity and low to normal body weight, even in absence of family history. The current study aimed to assess the autoantibody profile of these underweight/lean diabetic subjects, in order to better understand their aetiology. Methods: This cross sectional, observational study was carried out in endocrinology OPD and ward of RNT Medical College, Udaipur, Rajasthan (India). The study included consecutive 207 lean/underweight diabetic subjects, on insulin or oral antidiabetic drugs (OAD), with or without history of ketosis and negative family history of diabetes. After detailed history and anthropometric examination, subjects were screened for presence of autoantibodies to GAD, TPO and IgA tTG. Results: 9 subjects were excluded from analysis (7 pancreatic calcification, 2 incomplete data). Out of 198 subjects, 153 (77.3%) subjects tested positive for GAD antibodies, while Anti TPO and IgA anti tTG antibodies were positive in 50 (25.3%) and 6 (3.0%) subjects, respectively. 39 (19.69%) subjects tested positive for both anti GAD and anti TPO antibodies and only 1(0.505%) subject had all the 3 antibodies present. Of the total study population, 158 (79.8%) subjects were on insulin, while 13 (6.6%) subjects received OAD, and 27 (13.6%) subjects both insulin and OAD. Conclusions: Lean/underweight diabetic subjects with negative family history of diabetes should be screened for presence of autoimmune markers for type 1 diabetes mellitus, irrespective of their treatment.